Peptidoglycan recognition proteins in insect immunity. (February 2019) - Wang, Qiang; Ren, Meijia; Liu, Xiaoyong; Xia, Hengchuan; Chen, Keping
Highlights: The innate immunity of insects mainly depends on the interaction between the host's PRR and PAMP. PGRPs involve in Toll, IMD and PPO pathways. PGRPs plays an important role in the innate immunity of insects. Abstract: Insects lack an acquired immune system and rely solely on the innate immune system to combat microbial infection. The innate immunity of insects mainly depends on the interaction between the host's pattern recognition receptor (PRR) and pathogen-associated molecular pattern (PAMP). The peptidoglycan recognition proteins (PGRPs) family is the most important pattern recognition receptor (PRR) for insects. It can recognize the main component of the cell wall of the pathogenic microorganism, peptidoglycan (PGN), and plays an important role in the innate immunity of insects. In this paper, the structure, classification, and function of PGRPs is summarized, and the role of PGRPs in the innate immunity of insects is also discussed.